Charlotte Walsh likes to win : a novel - Piazza, Jo (Simon & Schuster, 2018)
"From Jo Piazza, the bestselling author of The Knock Off, How to Be Married, and Fitness Junkies, comes an exciting, insightful novel about what happens when a woman wants it all--political power, marriage, and happiness--but isn't sure just how much she's willing to sacrifice to get it. Charlotte Walsh is running for Senate in the most important race in the country during a midterm election that will decide the balance of power in Congress. Still reeling from a presidential election that shocked and divided the country and inspired by the chance to make a difference, she's left behind her high-powered job in Silicon Valley and returned, with her husband Max and their three young daughters, to her downtrodden Pennsylvania hometown to run in the Rust Belt state. Once the campaign gets underway, Charlotte is blindsided by just how dirty her opponent is willing to fight, how harshly she is judged by the press and her peers, and how exhausting it becomes to navigate a marriage with an increasingly ambivalent and often resentful husband. When the opposition uncovers a secret that could threaten not just her campaign but everything Charlotte holds dear, she has to decide just how badly she wants to win and at what cost. A searing, suspenseful story of political ambition, marriage, class, sexual politics, and infidelity, Charlotte Walsh Likes to Win is a glorious portrait of what it takes for a woman to run for national office in America today. Set amidst a disturbing political landscape unlike any other in history--with operatives who strive to win at any costs, an electorate that prefers disposable news, and unprecedented incivility from just about everyone--Jo Piazza has created an engrossing and timely novel for readers on both sides of the aisle"--